Analysis of Husband and Attitude Support to Pregnancy of Pregnant Women Gravidarum Hyperemesis in Kertosono Hospital - Yonni Siwi, Retno Palupi; Erma Retnaningtyas; Anggrawati Wulandari (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2021)
Every woman who is pregnant will experience a process of adjusting her body to pregnancy according to the stage of her current trimester. The first trimester is the beginning of the trimester which causes various responses in pregnant women. The occurrence of hyperemesis can increase anxiety in pregnant women. The purpose of this study is to analyze the influence of the influence of attitudes and support from husbands on anxiety of hyperemesis gravidarum pregnant women in Kertosono Hospital. The design of this research is a quantitative observational study with a cross sectional approach with the focus of the research being directed to analyze the influence of attitudes and support from husbands on the anxiety of hyperemesis gravidarum pregnant women at Kertosono Hospital with a population of 36 respondents and a sample of 32 respondents who were drawn using Accidental Sampling technique.Most of the respondents have a positive attitude as many as 23 respondents (71.9%). Half of the respondents have sufficient husband's support as many as 16 respondents (50%). Most of the respondents had moderate anxiety as many as 19 respondents (59.4%). The results of the study used the test Linear Regression shows that the p-value is 0.000 <0.05, then H1 is accepted, so it can be concluded that there is an effect simultaneously attitudes and support of husbands on anxiety of pregnant women with hyperemesis gravidarum in Kertosono Hospital with a magnitude of the influence of 86.5%. The existence of a good attitude from someone when experiencing an adverse event will determine the continuity in the future. And also with complaints of hyperemesis gravidarum that he experienced. So pregnant women are very important to be able to behave well and get support from their husbands well in order to control the anxiety experienced by pregnant women.